MENGANALISIS REFLECTIVE PRACTICE DALAM ORGANISASI PENDIDIKAN TERHADAP TRANSFORMASI PEMBELAJARAN: SYSTEMATIC LITERATURE REVIEW - Hadiraharja, Asep Riana; Yaya Warya; Bahar Nugraha Pradja; Ade Tutty R. R; Agus Mulyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reflective Practice in educational organizations is one of the important approaches in the transformation of modern learning that is adaptive, reflective, and based on digital innovation. This study aims to analyze the development of trends in reflective practice studies in educational organizations, identify the dominant factors that influence them, analyze the dynamics of the relationship between reflective practice, educational organizational culture, leadership, and digital transformation, and examine its impact on learning transformation. The research uses the Systematic Literature Review (SLR) approach with the PRISMA 2020 procedure. Data was obtained through the Scopus database using keywords related to reflective practice, pedagogical transformation, instructional design, and professional development. The results of the initial identification obtained 467 articles, then through the screening and eligibility process, 72 research reports were obtained. The results of the study show that reflective practice has experienced a paradigm expansion from individual reflection activities to educational organizational mechanisms that affect learning culture, professional development, pedagogical innovation, and digital transformation. The dominant factors influencing reflective practice include transformational leadership, collaborative organizational culture, digital education technology, and constructivistic learning approaches. In addition, reflective practice has been proven to have an impact on increasing student engagement, higher order thinking skills, creativity, active learning, and experiential learning transformation. This study concludes that reflective practice has a strategic position in building educational organizations that are reflective, innovative, adaptive, and oriented towards the transformation of 21st century learning. Keywords: reflective practice, educational organization, learning transformation, educational leadership, digital transformation, systematic literature review